Rotatory 3D structured mesh study using openFOAM to simulate the flow in francis turbine. (2022) - Hidalgo, V.; Velasco, M.; Cando, E.; Valencia, E.; Simbaña, S.; Puga, D.; Mora, C.; Escaler, X.
Abstract: The development of a methodology to simulate numerically the steady state flow field in Francis turbines was carried out using the open source CFD software OpenFOAM along with a MRF and AMI approach. A structured mesh obtained from previous studies was used with some modifications to solve the presence of imbalance points in the simulation. Numerical simulations using the SIMPLE algorithm were performed together with two different turbulence models. It was confirmed that the results obtained reproduced the phenomenon with a great approximation and predicted the output load with only a deviation of around 5.02% against experimental data.